2015
DOI: 10.17554/j.issn.2410-0579.2015.01.12
|View full text |Cite
|
Sign up to set email alerts
|

βENaC Acts as a Mechanosensor in Renal Vascular Smooth Muscle Cells That Contributes to Renal Myogenic Blood Flow Regulation, Protection From Renal Injury and Hypertension

Abstract: Pressure-induced constriction (also known as the “myogenic response”) is an important mechanodependent response in small renal arteries and arterioles. The response is initiated by vascular smooth muscle cell (VSMC) stretch due to an increase in intraluminal pressure and leads to vasoconstriction. The myogenic response has two important roles as a mechanism of local blood flow autoregulation and protection against systemic blood pressure-induced microvascular damage. However, the molecular mechanisms underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Another possibility may relate to evidence showing that AngII reduces immunolabeled βENaC in renal vascular smooth muscle [30]. This is potentially important because βENaC is an essential component of the vascular mechanosensor that contributes to the myogenic response [31], and we previously showed that βENaC protein expression is lower in cerebral arteries from placental ischemic rats when compared with normal pregnant rats [17]. Therefore, if cerebral vascular responses to AngII mirror those in the renal vasculature, it may be that angiotensin mediated downregulation of βENaC is a contributing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility may relate to evidence showing that AngII reduces immunolabeled βENaC in renal vascular smooth muscle [30]. This is potentially important because βENaC is an essential component of the vascular mechanosensor that contributes to the myogenic response [31], and we previously showed that βENaC protein expression is lower in cerebral arteries from placental ischemic rats when compared with normal pregnant rats [17]. Therefore, if cerebral vascular responses to AngII mirror those in the renal vasculature, it may be that angiotensin mediated downregulation of βENaC is a contributing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A number of ion channels have been proposed to contribute to pressure-induced depolarization of VSMCs (Harder, 1984;Knot and Nelson, 1998;Kotecha and Hill, 2005) including: members of the transient receptor potential (TRP)-family of cation channels, such as TRPC6 (Welsh et al, 2002;Gonzales et al, 2014), TRPM4 (Earley et al, 2004;Gonzales et al, 2014), TRPV2 (McGahon et al, 2016), and TRPV4 (Soni et al, 2017); members of the degenerin family of channels including the epithelial Na + channel (ENaC) family Drummond, 2005, 2006;VanLandingham et al, 2009;Drummond and Stec, 2015), the acid-sensitive ion channel (ASIC) family of channels (Gannon et al, 2015), and purinergic P 2 X 7 Purinergic Receptor (P 2 X 7 ) channels (Kauffenstein et al, 2016; Figure 2). In addition, Ca 2+ -activated Cl − channels (CaCC; ANO1/TMEM16A) may be activated by Ca 2+ influx through TRPC6 channels (Bulley et al, 2012;Wang et al, 2016) and also contribute to pressureinduced depolarization of VSMCs (Figure 2).…”
Section: Which Ion Channels Contribute To Pressure-induced Membrane Depolarization?mentioning
confidence: 99%
“…The expression of ENaC in smooth muscle cells has been shown in many organs including vascular smooth muscle (Drummond, Grifoni, & Jernigan, 2008; Kusche‐Vihrog, Tarjus, Fels, & Jaisser, 2014), epididymis (Sharma & Hanukoglu, 2019), arrector pili muscle cells in skin (Hanukoglu et al, 2017), and renal microvascular smooth muscle cells (Guan, Pollock, Cook, Hobbs, & Inscho, 2009). It has been suggested that ENaC functions as a mechanosensor in vascular smooth muscle cells that initiate pressure‐induced constriction known as the “myogenic response” (Drummond & Stec, 2015). Extending these earlier findings, we suggest that ENaC has a role in the function of vas deferens smooth muscle cells that remain to be defined.…”
Section: Discussionmentioning
confidence: 99%